1995
DOI: 10.1006/viro.1995.1199
|View full text |Cite
|
Sign up to set email alerts
|

Avian Reovirus σC Protein Contains a Putative Fusion Sequence and Induces Fusion when Expressed in Mammalian Cells

Abstract: The biological functions of the structural protein sigma C, from avian reovirus strain RAM-1, were investigated in this study. A putative fusion peptide in sigma C was recognized in the deduced amino acid sequence by homology with Pneumovirus fusion sequences, and it was thus postulated that this protein may be involved in the formation of syncytia in cells infected with RAM-1. The sigma C gene was cloned and expressed in mammalian (COS7) cells and the sigma C protein was found to induce syncytia. It was there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Avian reovirus, together with two mammalian reoviruses, Nelson Bay virus and baboon reovirus, are fusogenic viruses that induce syncytia formation in infected cells (Duncan et al, 1995;Gard and Compans, 1970;Kamawara et al, 1965). Recent studies have revealed that the fusogenic activity of avian reovirus is associated with genome segment S1 (Duncan and Sullivan, 1998;Shmulevitz and Duncan, 2000), and two of the S1-encoded proteins, C and p10, were reported to display fusogenic activity (Meanger et al, 1999;Shmulevitz and Duncan, 2000;Theophilos et al, 1995). The third goal of this study was therefore to investigate the fusogenic properties of the proteins encoded by the three S1 ORFs.…”
Section: Introductionmentioning
confidence: 98%
“…Avian reovirus, together with two mammalian reoviruses, Nelson Bay virus and baboon reovirus, are fusogenic viruses that induce syncytia formation in infected cells (Duncan et al, 1995;Gard and Compans, 1970;Kamawara et al, 1965). Recent studies have revealed that the fusogenic activity of avian reovirus is associated with genome segment S1 (Duncan and Sullivan, 1998;Shmulevitz and Duncan, 2000), and two of the S1-encoded proteins, C and p10, were reported to display fusogenic activity (Meanger et al, 1999;Shmulevitz and Duncan, 2000;Theophilos et al, 1995). The third goal of this study was therefore to investigate the fusogenic properties of the proteins encoded by the three S1 ORFs.…”
Section: Introductionmentioning
confidence: 98%
“…The ARV S1 gene also encodes proteins p10 and p17. Although ARVs share many features with the prototypic mammalian reoviruses (MRV), several notable differences exist including host range, pathogenicity, hemagglutination properties, and syncytium formation (Ni and Ramig, 1993;Theophilos et al, 1995;Martinez-Costas et al, 1997a;Jones, 2000;van der, 2000). Genomic coding differences also exist between MRV and ARV.…”
Section: Introductionmentioning
confidence: 99%
“…At least ten structural polypeptides were identified in the latter study. The minor outer-capsid polypeptide σC was shown to be the cellattachment protein and to induce serotype-specific neutralizing antibodies Wickramasinghe et al, 1993 ;Theophilos et al, 1995). This protein was suggested to be structurally analogous to mammalian σ1 Shapouri et al, 1995).…”
Section: Introductionmentioning
confidence: 99%